Research on the Ecological Protection of Coal Gangue Slope Based on a Polymer Curing Agent - Jian Zhang; Wen Yi; Weijia Yuan; Yifang Liu; Zifan Sui (Advances in Materials Science and Engineering)
To improve the ecological protection of coal gangue slopes, this work developed a polymer curing agent using a pure acrylic emulsion and cement as the main raw materials. By testing the workability, waterproofing, durability, and adhesion of the curing agent with different polymer-to-cement ratios, the optimum mixing ratio of the polymer curing agent was obtained, and the protection mechanism was analysed based on the test results and by scanning electron microscopy (SEM). Then, simulated slope and practical engineering applications were carried out. The results show that pure acrylic emulsion curing agent with a polymer-to-cement ratio of 6 : 5 is most suitable for the ecological protection of coal gangue slopes. The polymer curing agent can form a network structure film layer with a good waterproofing effect on the coal gangue surface. Simultaneously, the network structure film layer can reduce the influence of weathering and leaching on the coal gangue, prevent the heavy metal elements in coal gangue from entering the surrounding soil, improve the growth environment of plants, and improve the effect of ecological restoration. This research can be applied to the ecological protection of coal gangue slopes.